Readings in social theory - edited with introductions by James Farganis; Vassar College (McGraw-Hill, 2008)
This highly regarded anthology of primary readings in sociological theory covers the major theorists and schools from classic to contemporary, modernist, and postmodernist, in a chronological organization. Its comprehensive coverage and excellent introductions make this book appealing as a main text for professors who want to encourage students to read and interpret original sources, or as a supplement for those who use a traditional main text